2022
DOI: 10.1038/s41598-022-09490-5
|View full text |Cite
|
Sign up to set email alerts
|

UV-induced local immunosuppression in the tumour microenvironment of eccrine porocarcinoma and poroma

Abstract: Eccrine porocarcinoma (EPC) is a rare malignant adnexal tumour of the skin. Part of EPCs develop from their benign counterpart, poroma (EP), with chronic light exposure and immunosuppression hypothesized to play a role in the malignant transformation. However, the impact of chronic light exposure on the microenvironment of EPCs and EPs has not been investigated yet. Although the clinical relevance of tumour infiltrating lymphocytes (TILs) and tertiary lymphoid structures (TLSs) has been established in various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
5
0
2
Order By: Relevance
“…This is because the most common sites for PC are sun-exposed areas (the head, neck, and extremities). Puttonen et al found a negative correlation between UV damage and tumor-infiltrating lymphocytes (TILs) [ 22 ]. The results suggest that UV has a potentially immunosuppressive effect on PC microenvironments.…”
Section: Pathogenesismentioning
confidence: 99%
“…This is because the most common sites for PC are sun-exposed areas (the head, neck, and extremities). Puttonen et al found a negative correlation between UV damage and tumor-infiltrating lymphocytes (TILs) [ 22 ]. The results suggest that UV has a potentially immunosuppressive effect on PC microenvironments.…”
Section: Pathogenesismentioning
confidence: 99%
“…The results of the present study underline the power of gene expression profiling in solid tumors and increase understanding of the genetic architecture of EP, thus advancing efforts to translate molecular findings into prospective clinical trials of novel agents and promising treatment strategies 11,44 . However, the highly variable clinical presentation of EP often impedes early diagnosis, and the steps that lead to EP transformation remain poorly understood 7,10,17,45 . To dissect the stages of EP carcinogenesis, we followed up our gene expression profiling results in a cohort of EPO samples.…”
Section: Discussionmentioning
confidence: 89%
“…In another study, Puttonen et al investigated the distribution and significance of tumor infiltrating lymphocytes (TILs) in the EPC microenvironment, assuming that an altered immunological environment could explain the involvement of chronic UV radiation in the tumorigenesis of EPC. Unlike the known association of TILs with positive prognosis in various skin tumors, such as melanoma and MCC, the authors observed a negative correlation between UV damage and TIL density in EPCs, supporting the immunosuppressive effect of UV radiation on the microenvironment of these tumors [ 27 ].…”
Section: Pathogenesis—risk Factorsmentioning
confidence: 89%